Penerapan Budidaya Ikan Hias Beserta Sosialisasi GEMARI Melalui Program Mandiri Kampus Mengajar Angkatan VI 2023 - Risqi Mutmainnah Mansur; Isti Adelia; Yusdalifa Ekayanti Yunus; Ummu Kaltsum SC; Kamaruddin Hasan; Adi Irwandi; Muhammad Yusuf Yunus (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities through the Teaching Campus (KM) program. The application of ornamental fish farming accompanied by the socialization of fond of eating fish aims to increase community knowledge within the scope of placement schools regarding the benefits of eating fish. This activity has provided students with the experience of learning and working and mingling directly with the community. The placement of the program is SDN 122 BARRU which is located in Batupute Village, SoppengRiaja District, Barru Regency, South Sulawesi Province. The results of community service activities through the KM program in the field of aquacultureare increasing public awareness of the importance of eating fish to increase nutrition and prevent stunting.